Overvoltage Mitigation Filter Using High-Frequency Cable Modeling in Long Transmission Lines for Silicon Carbide Inverter Systems - Lee, Yun Jin; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2025)
This paper analyzes a design of overvoltage mitigation filter using high-frequency cable modeling in long transmission lines for silicon carbide inverter systems. The SiC inverter systems operating with long transmission lines may experience overvoltage caused by voltage reflection, leading to insulation breakdown. The proposed method to address the problem of overvoltage occurring on long transmission lines involves connecting a RLC filter at the end of the cable to reduce the overvoltage. The RLC filter is calculated by deriving the characteristic impedance using the parameters of the cable modeling. The validity of cable modeling and designing overvoltage mitigation filter is verified through simulation results.
Keywords: Cable model; Filter; High frequency HF; Inverter system; Long transmission lines; Over-voltages; Overvoltage mitigations; Paper analysis; Reflected voltage; SiC MOSFETs; cable modeling; filter; overvoltage; reflected voltage; SiC MOSFET